The Effect of Intellectual Capital, Debt to Equity Ratio, Total Asset Turnover and Current Ratio on Profitability in LQ45 Companies Listed on the Indonesia Stock Exchange - Khotimah, Maufiroh Titik; Adam, Mohamad; Widiyanti, Marlina; Thamrin, Kemas Muhammad Husni (Jurnal Multidisiplin Indonesia, 2024)
The purpose of this study is to obtain empirical evidence of Intellectual Capital, Debt to Equity Ratio, Total Asset Turnover, Current Ratio on Return on Asset listed on LQ45 the Indonesia Stock Exchange. The sampling technique used purposive sampling, the research samples obtained totaled 20 companies with quarterly research period from 2020-2022 so that there were 60 units of analysis. The research design was quantitative descriptive. The analysis technique in this research is multiple regression analysis method. The results showed that IC and TATO has a significant positive effect on Profitability, DER and CR have no effect on profitability. The implication of this research is that companies must pay attention to IC and TATO that can affect profitability so that company profitability can increase.